Modeling, Simulation and Optimization of Complex Processes - Bock, Hans Georg; Phu, Hoang Xuan; Rannacher, Rolf (Springer, 2012)
Modeling, Simulation and Optimization of Complex Processes; Proceedings of the Fourth InternationalConference on High Performance Scientific Computing, March 2-6, 2009, Hanoi, Vietnam; Preface; Contents; A Cutting Hyperplane Method for Generalized Monotone Nonlipschitzian Multivalued Variational Inequalities; 1 Introduction; 2 Generalized Monotonicity and Algorithm; 3 Convergence of the Algorithm; 4 An Application to Nonlinear Complementarity Problems; References; Robust Parameter Estimation Based on Huber Estimator in Systems of Differential Equations; 1 Motivation
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2009 -- Hanoi; Wissenschaftliches Rechnen